2012
DOI: 10.1007/s00586-012-2583-6
|View full text |Cite
|
Sign up to set email alerts
|

In vivo analysis of cervical kinematics after implantation of a minimally constrained cervical artificial disc replacement

Abstract: Introduction To better understand cervical kinematics following cervical disc replacement (CDR), the in vivo behavior of a minimally constrained CDR was assessed. Methods Radiographic analysis of 19 patients undergoing a 1-level CDR from C4-5 to C6-7 (DISCOVER, DepuySpine, USA) was performed. Neutral-lateral and flexionextension radiographs obtained at preop, postop and late follow-up were analyzed for segmental angle and global angle (GA C2-7). Flexion-extension range of motion was analyzed using validated qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
2
19
0
Order By: Relevance
“…patients had an HO grade greater than grade II and HO was a significant risk factor for RASP development. Recent in vivo analysis of cervical kinematics after minimally constrained CDA showed that maintaining physiological COR is difficult, whereas both angular and translation motion can be maintained or restored [28]. Theoretically, an ideal CDA surgical result simulates the intervertebral disk functions in term of ROM, COR, and shock absorption.…”
Section: Discussionmentioning
confidence: 95%
“…patients had an HO grade greater than grade II and HO was a significant risk factor for RASP development. Recent in vivo analysis of cervical kinematics after minimally constrained CDA showed that maintaining physiological COR is difficult, whereas both angular and translation motion can be maintained or restored [28]. Theoretically, an ideal CDA surgical result simulates the intervertebral disk functions in term of ROM, COR, and shock absorption.…”
Section: Discussionmentioning
confidence: 95%
“…However, an imprecise position of the implant may cause a negatively altered COR and perhaps influence HO formation. Assuming that replication of a physiologic COR is an important design feature of a cervical prosthesis, Koller et al found that ideal surgical preparation and ideal positioning of the implant are most important to preserve the segmental COR and balance [19].…”
Section: Discussionmentioning
confidence: 99%
“…Lateral motion is limited to 21°. The fixed inlay in combination with a ball-and-socket superior articulation with limited lateral motion has resulted in the device being described as minimally constrained [19].…”
Section: The Arthroplasty Devicementioning
confidence: 99%
“…Although cervical arthroplasty has an advantage over ACDF in retaining cervical motion quality, the implant position and type of prosthesis in cervical arthroplasty impact cervical motion quality postoperatively. Different rotation centers in the prevalent artificial cervical discs produce different biomechanical performances.…”
Section: Clinical Application Of Kinematic Quality Parameters In Diffmentioning
confidence: 99%